Identification of novel major and minor quantitative trait loci associated with bacterial blight resistance in rice from Oryza nivara‐derived wild introgression lines. (21st September 2022) - Balakrishnan, Divya; Laha, Gouri Sankar; Arra, Yugander; Surapaneni, Malathi; Beerelli, Kavitha; Ladhalakshmi, Duraisamy; Srinivas Prasad, Madamsetty; Subba Rao, Lella Venkata; Sundaram, Raman Meenakshi; Neelamraju, Sarla
Abstract: Wild species are known to be reservoir for agronomically important traits including disease resistance in crops. Bacterial blight (BB) is one of the major diseases of rice causing significant yield reduction, and host plant resistance plays a major role in the management of the disease. In this study, we employed backcross introgression lines (BILs) of 'Swarna' containing wild introgressions from two accessions of Oryza nivara IRGC81848 and IRGC81832 in order to map quantitative trait loci (QTLs) for BB resistance. A total of 22 and 43 QTLs for BB resistance were detected respectively on 12 chromosomes, which explained between 2.5% to 18.09% of the phenotypic variance in the two populations. Of the significant QTLs, qBB‐1‐1 (RM259‐RM9) and qBB‐10‐1 (RM474‐RM271) were detected across the two populations and the resistance contributing alleles were from donor wild accessions. Two major QTLs in 'Swarna'/ O. nivara IRGC81848 (NPS lines) and seven QTLs in 'Swarna'/ O. nivara IRGC81832 (NPK lines) were consistently detected across the years in the respective populations. Novel QTLs qBB‐10‐1 and qBB‐12‐1 are identified as candidate genomic regions for further fine mapping. These stable QTLs identified can be utilized for enhancing BB resistance in elite rice genotypes via marker‐assisted or genomic selection strategies.